2005
DOI: 10.3748/wjg.11.5095
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional aspects of the liver and liver sinusoidal cells in relation to colon carcinoma metastasis

Abstract: Nowadays, liver metastasis remains difficult to cure. When tumor cells escape and arrive in the liver sinusoids, they encounter the local defense mechanism specific to the liver. The sinusoidal cells have been widely described in physiologic conditions and in relation to metastasis during the past 30 years. This paper provides an "overview" of how these cells function in health and in diseases such as liver metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Our previous microscopy and fine structural immunochemistry studies significantly contributed to the above model and as depicted in figure 1 we were able to demonstrate that KC, NK and HECs all work together in concert as one immune-surveillance guardian in the defence against CRC liver metastasis ( Figure 1) [6] . Furthermore, it was shown that phagocytosis and apoptosis are key processes in three central steps in the complex CRC liver metastatic cascade, briefly: (Step Ⅰ) When CC531s colon carcinoma cells encounter the liver sinusoid about 90% of the tumour cells are eliminated by a synergistic action between KC and NK cells [9] ; (Step Ⅱ) We have proven that HECs express FasL and that about 5% of the colorectal CC531s cell population express functional Fas under influence of IFNγ and NO released in the sinusoid by NK and HECs, respectively.…”
Section: Phagocytosis Apoptosis Endothelial Retraction and Tumour Smentioning
confidence: 70%
See 1 more Smart Citation
“…Our previous microscopy and fine structural immunochemistry studies significantly contributed to the above model and as depicted in figure 1 we were able to demonstrate that KC, NK and HECs all work together in concert as one immune-surveillance guardian in the defence against CRC liver metastasis ( Figure 1) [6] . Furthermore, it was shown that phagocytosis and apoptosis are key processes in three central steps in the complex CRC liver metastatic cascade, briefly: (Step Ⅰ) When CC531s colon carcinoma cells encounter the liver sinusoid about 90% of the tumour cells are eliminated by a synergistic action between KC and NK cells [9] ; (Step Ⅱ) We have proven that HECs express FasL and that about 5% of the colorectal CC531s cell population express functional Fas under influence of IFNγ and NO released in the sinusoid by NK and HECs, respectively.…”
Section: Phagocytosis Apoptosis Endothelial Retraction and Tumour Smentioning
confidence: 70%
“…This hepatic sinusoidal immune system involves the hepatic-specific natural killer cells (NK) (pit cells) [3] , Kupffer cells (KC) (liver-associated macrophages) [4] and hepatic endothelial cells (HEC) [5] , and is proven to play an important role in protecting the liver from invading colon carcinoma cells [6] . The conventional paradigm of CRC liver metastasis is based on a multi-step process characterized by a series of structural, cellular and molecular events, which give the tumour cells the ability to proceed through the many phases of liver metastasis.…”
Section: Colorectal Cancer and The Hepatic Sinusoidal Immune Systemmentioning
confidence: 99%
“…Each of these cell types plays a crucial role in hepatic homeostasis and CRC metastasis [113] . The progression of CRC hepatic metastasis is divided into four interrelated phases: (1) microvascular phase of liver-infiltrating malignant cells; (2) interlobular micrometastasis phase; (3) angiogenic micrometastasis phase; and (4) established hepatic metastasis phase.…”
Section: Extravasation -Crc Cell Arrest In the Hepatic Sinusoidsmentioning
confidence: 99%
“…The cells contain granules with lysosomal enzymes, perforin and various phosphatases, but their structural characteristic is the presence of cytoplasmic rod vesicles. Their shape varies, due to the presence of pseudopodia [113,168,169] . Pit cells substantially contribute to hepatic immunity and exert strong antitumour action.…”
Section: Pit Cellsmentioning
confidence: 99%
“…Leukocyte recruitment upon liver injury [4], [5], [6] as well as liver colonization by metastatic tumor cells [7], [8] are actively influenced by LSECs. The unique morphology as well as the microenvironment-dependent molecular differentiation of LSECs [19] define the organ-specific features of this transendothelial barrier.…”
Section: Introductionmentioning
confidence: 99%